Factors that affect student performance: The implementation of the l-learn at a local university / Mariam Setapa, Noorita Mohammad and Khairunnisa Rahman - Setapa, Mariam; Mohammad, Noorita; Rahman, Khairunnisa (Research Management Institute (RMI), 2012)
The purpose of this study is to identify factors affecting the usage of I-Learn in UiTM towards students' performance. In Universiti Teknologi MARA (UiTM), it's known as i- Learn method. A study conducted by Hafizah Mohamad Hsbollah and Kamil Md. Idris (2009) found that there were six factors that influence the use of e-learning among the lecturers. Therefore, this study also will examine these factors in terms of university students. These factors are technological features and characteristics of the individual (students). From the pilot study conducted on 20 students of UiTM Johor, found that students are aware of the system, but do not practice it in total for various reasons. Therefore, this study is to identify the factors affecting the usage of i-Learn in UiTM towards students' performance and to determine the most dominant factor affecting the usage of i-Learn in UiTM towards students' performance. Data collected from students of Universiti Teknologi MARA Johor only. Students involved in this study are students from Semester 1 (Part 1) a total of 60 persons consisting of two groups of students. Pilot test was conducted on 20 students to test the validity of questionnaire. In addition, the internal consistency using Cronbach Alpha and exploratory factor analysis will also used to verify the measurement used later. In addition, correlation and regression methods used to identify the factors under study and to determine the most dominant factor affecting the usage of i-Learn in UiTM towards students' performance. An expected result of this study was to see a clear correlation factors are reviewed with student performance.